Nano-Additives in Asphalt Binder: Bridging the Gap between Traditional Materials and Modern Requirements - Albayati, Amjad H.; Latief, Roaa H.; Al-Mosawe, Hasan; Wang, Yu (Applied sciences, 2024)
This research delves into the realm of asphalt technology, exploring the potential of nano-additives to enhance traditional asphalt binder properties. Focusing on Nano-Titanium Dioxide (NT), Nano-Aluminum Oxide (NA), and Nano-Silica Oxide (NS), this study investigates the effects of incorporating these nanomaterials at varying dosages, ranging from 0% to 8%, on the asphalt binder’s performance. This study employs a series of experimental tests, including consistency, storage stability, rotational viscosity, mass loss due to aging, and rheological properties, to assess the impact of nano-additives on asphalt binder characteristics. The findings indicate a substantial improvement in the consistency of the asphalt binder with the addition of nanomaterials, particularly NS, which shows a 41% reduction in penetration at an 8% content and a notable increase in the softening point. The storage stability tests reveal that NS-modified asphalt exhibits superior stability compared to NT and NA, with a significantly lower ΔT increase. Furthermore, the investigation into rotational viscosity suggests that NS, despite increasing the binder’s viscosity, does not exceed the AASHTO M320 threshold, ensuring the binder’s workability. Aging tests demonstrate that NT, at lower concentrations, acts as an effective anti-aging agent, whereas NA and NS tend to increase the mass loss, impacting thermal stability. This study concludes that while each nanomaterial uniquely influences the asphalt binder’s properties, NS stands out in terms of enhancing the high-temperature performance and storage stability. Optimal dosages of 6% for NT and NA and 4% for NS are recommended based on the Overall Desirability analysis. This research bridges the gap between traditional asphalt materials and modern requirements, highlighting the transformative impact of nano-additives in advancing asphalt pavement technology.